Analisis Kepercayaan Konsumen terhadap Transaksi E-Commerce di Indonesia dalam Perspektif Etika Bisnis Islam - Rhedisya Maharani; Budi Jaya Putra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The growth of e-commerce in Indonesia has transformed people’s transaction patterns through the use of digital technology, which offers convenience, efficiency, and a broader market reach. On the other hand, the nature of digital transactions which involve minimal direct interaction gives rise to various risks that could potentially affect consumer trust. This study aims to analyze consumer trust in e-commerce transactions in Indonesia from the perspective of Islamic business ethics. The study employs a qualitative approach based on a literature review, examining various scientific journals, academic books, and relevant sources related to e-commerce, consumer trust, and Islamic business ethics. The analysis was conducted through the identification, categorization, synthesis, and critical interpretation of the selected literature. The results indicate that consumer trust is formed through the interaction of technical, social, institutional, and moral factors. The principles of siddiq, amanah, tabligh, fathanah, justice, and maqashid syariah play a crucial role in mitigating transaction risks, strengthening consumer protection, enhancing satisfaction and loyalty, and supporting the sustainability of the e-commerce ecosystem. These findings affirm that Islamic business ethics serve a strategic function as a normative and operational foundation for building consumer trust in digital commerce.